EKSEKUSI PUTUSAN PENGADILAN TATA USAHA NEGARA TERHADAP SENGKETA PERTANAHAN MENURUT HUKUM POSITIF DI INDONESIA (STUDI KASUS PUTUSAN PENGADILAN TATA USAHA NEGARA NOMOR 188 PK/TUN/2018) - Eva Fortuna Kasan; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
The administrative court is one of the courts under the judistrication of the judiciary which its task is to resolve disputes that occur both within the internal environment of State Administrative Officials as well as disputes that occur between State Administrative Officials and Individuals or Civil Law Entities. The disputes that often occur between State Administrative Officials and Individuals or Civil Legal Entities are regarding land disputes caused by the mistake made by State Administrative Officials, one of which is regarding overlapping land rights. As a result of the overlapping land rights, the dispute will be brought to the State Administrative Court to obtain tha permanent legal decision, the problem regarding the amount of decisions of the State Administrative Court that cannot be executed arise. Research shows the data regarding the regulation execution of State Administrative Court Decisions in Indonesia is weak. The efforts on forcing State Administrative Officials to execute court decisions that already have the power of permanent legal status have not been executed optimally. Therefore, Indonesia needs to formulate a new law that includes regulations for the execution of decisions of the State Administrative Court